Hawk of the Mind Collected Poems - Mu, Yang (Modern Chinese Literature from Taiwan, 2018)
Yang Mu is a towering figure in modern Chinese poetry. His poetic voice is subtle and lyrical, and his work is rich with precise images and crystalline thoughts invoking temporality and remembrance. A bold innovator and superb craftsman, he elegantly combines cosmopolitan experimentation with poetic forms and an allusive reverence for classical Chinese poetry while remaining rooted in his native Taiwan and its colonial history.Hawk of the Mind is a comprehensive collection of Yang Mu’s poetry that presents crucial works from the many stages of his long creative career, rendered into English by a team of distinguished translators. It conveys the complexity and beauty of Yang Mu’s work in a stately and lucid English poetic register that displays his ability to range from meditative to playful and colloquial to archaic. The volume includes an editor’s introduction and definitive commentary that offer insights into the poet’s major themes and motifs, explaining how he draws on deep engagement with Chinese and Western literary traditions, history, and art as well as mythology, philosophy, and music and a profound love for the natural world to create a nuanced and multifaceted artistic universe. It also contains translations of prefaces and afterwords written by Yang Mu for collections of his poetry. Hawk of the Mind demonstrates the breadth and depth of Yang Mu’s oeuvre, illustrating the distinctive style and affective power of a great poet